The Alignment Between Nursing Students' Field Practices and the Needs of the 2030 HIV/AIDS-Free Era - Halitopo, Yoel; Felle, Zeth Roberth; Auparai, Nuriati Sarlota (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: The involvement of nursing students in field practice needs to be questioned in the era approaching HIV/AIDS-free 20230. Objective: This research aims to determine the correlation between student practices and the field needs of the 2030 HIV/AIDS free program.  Methods: This research used quantitative methods with a correlational design. The population was students from the Jayapura Ministry of Health Polytechnic in Wamena, Papua Mountains province. The sample was 180 nursing students. The dependent variable was the needs of the field in an HIV/AIDS-free era. The independent variable was Student field practice. The research instrument was a questionnaire distributed online using Google Forms. The data was processed using univariate, bivariate, and analyzed using Pearson'n Product Moment with the help of SPSS version 25. Results: The analysis of Pearson's Product Moment show a p-value of 0.000, which means p-value <0.05, which means H0 is rejected. There is an influence between Student field practice and the field needs of the HIV/AIDS 2030-free Era. The Pearson correlation coefficient (r) value is positive 0.830. Conclusion: The study recommended that the association between student field practice and the field needs of the HIV/AIDS 2030-free era is in the 'low/weak' category